Fractional variational iteration method and its application to fractional partial differential equation - Elbeleze, Asma Ali; Kilicman, Adem; M. Taib, Bachok (Hindawi Publishing Corporation, 2013)
We use the fractional variational iteration method (FVIM) with modified Riemann-Liouville derivative to solve some equations in fluid mechanics and in financial models. The fractional derivatives are described in Riemann-Liouville sense. To show the efficiency of the considered method, some examples that include the fractional Klein-Gordon equation, fractional Burgers equation, and fractional Black-Scholes equation are investigated.